STRATEGI MENGEMBANGKAN IKLIM INVESTASI YANG KONDUSIF UNTUK OTONOMI YANG BERORIENTASI PADA KEMAKMURAN MASYARAKAT DI KABUPATEN BANGKALAN - Wasil, Muhammad (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2013)
The role of investment is very important to encourage economic development of a region. Bangkalan be the entrance to the area of Surabaya to Madura through longest bridge or crossing Kamal. The existence longest bridge is not enough become levers of economic activity in the region Bangkalan, investors are still reluctant to invest and invest in this region. Conducive investment is a good implementation of regional autonomy at the same time a real effort for the welfare of the communities in the region. The purpose of research to identify services and types of licenses associated with the investment and identifying potential local resources Bangkalan. Recommendation of this study is the need for simplifying the licensing service that is fast, safe and cheap, service-based licensing site / on-line in order to be accessible at any time without being limited by space and time. Lanjuran's research potential of the region in accordance with the mapping of the resource area so that services become more focused investments, investment offers to investors become more organized and easier to control the investment climate is conducive sertra get service model of the behavior of investment to improve regional autonomy capable of providing welfare for society